Transcranial duplex sonography and CT angiography in acute stroke patients - Bar, Michal; Skoloudík, David; Roubec, Martin; Hradílek, Pavel; Chmelová, Jana; Czerný, Daniel; Procházka, Václav; Langová, Katerina; Herzig, Roman (Journal of neuroimaging, 2010)
Acute occlusion of cervical or intracranial arteries is the most common cause of ischemic stroke (IS). The aims of the current study were to compare the occurrence of acute pathologic findings in intracranial arteries using transcranial color-coded sonography (TCCS) and computed tomographic angiography (CTA) performed within 3 hours of IS onset and to assess the correlation between the vascular findings on admission and the patient's clinical state on admission and 3 months after the IS. Forty-five consecutive patients with an acute IS were included in the prospective study during an 18-month period. All patients underwent CTA and TCCS within the first 3 hours of symptom onset. A high rate of pathologic findings in the intracranial circulation was found (70.9% in CTA and 77.4% in TCCS examinations). The CTA and TCCS findings with respect to the intracranial arteries were consistent in 87.1% of cases (Cohen's kappa, .797). The sensitivity, specificity, and positive and negative predictive values achieved with TCCS in patients with middle cerebral artery main stem occlusion were 92.3%, 94.4%, and 92.3% and 94.4%, respectively. There was no correlation between the patient's clinical status on admission and 3 months after the onset of the IS and the CTA or the TCCS findings (P > .1 in all cases). A substantial agreement was found between TCCS and CTA in the detection of pathologic findings in intracranial vessels in acute stroke patients. Both methods can be used for this purpose.
Keywords: Aged; Aged, 80 and over; prediktivní hodnota testů; výběr pacientů; lidé; lidé středního věku; senioři; ženské pohlaví; mladiství; Sensitivity and Specificity; Ultrasonography, Doppler, Color; Adolescent; Female; mužské pohlaví; Ultrasonography, Doppler, Transcranial; mozková angiografie; Patient Selection; Adult; cévní mozková příhoda; Middle Aged; senioři nad 80 let; ultrasonografie dopplerovská barevná; Humans; Predictive Value of Tests; Stroke; prospektivní studie; Cerebral Angiography; dospělí; Male; senzitivita a specificita; ultrasonografie dopplerovská transkraniální; Prospective Studies